Penguatan Pengendalian Persediaan Obat melalui Integrasi ABC-VEN, EOQ, dan ROP di Rumah Sakit Rujukan Nasional - Rasendah, Rasendah; Andriani, Helen; Andriyanto, Dendhi Bagus (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2026)
Drug inventory control is a critical component of pharmaceutical management in referral hospitals with high service complexity. This study aimed to evaluate pharmaceutical inventory control performance at the Pharmacy Installation of RSUP Persahabatan and to formulate improvement strategies using an Operational Research approach. A mixed-methods design with a sequential explanatory approach was applied. Quantitative analysis was conducted on 2,291 drug items recorded in the inventory system during October 2025 using ABC-VEN classification to identify priority medicines, followed by calculations of Economic Order Quantity (EOQ) and Reorder Point (ROP). Qualitative data were obtained through in-depth interviews with key informants to strengthen the interpretation of quantitative findings. The results showed that 131 Pareto A medicines had an investment value of IDR 6,788,411,815, indicating a high concentration of inventory investment in a small proportion of items. In addition, stagnant stock was identified in 211 drug items with a total investment value of IDR 444,994,656, while stock out events accounted for 11.25% of total drug items. EOQ and ROP calculations revealed substantial variation across drug items, reflecting differences in demand characteristics, investment value, and procurement lead times, indicating that uniform ordering policies are not appropriate. Scenario-based simulations demonstrated that integrating ABC-VEN, EOQ, and ROP has the potential to improve inventory management efficiency, reduce the risks of stock outs and stagnant stock, and support the continuity of hospital pharmaceutical services.